Feeding the World Well : A Framework for Ethical Food Systems - Wychgram, Cara, 1988-; Goldberg, Alan M. (Food ethics., 2020)
"This edited collection advances the discussion of ethical food production and the many elements that have to be balanced in order to achieve it. A large group of contributors from academia and industry prepare the food production industry for a world in which "ethical" or "sustainable" production practices are not only trendy but necessary to ensuring that we can feed the world's growing population"--